Analiza możliwości wykorzystania kanału ściekowego jako dolnego źródła dla pompy ciepła systemu zasilania CO i CWU wybranego budynku oraz projekt koncepcyjny - Madejski, Mateusz (My University, 2011)
The main aim of this project is analyze the possibility of use the sewer as the waste heat. Presented the locations and ways of receive heat. Moreover, was disccussed characteristics of the heat pump and also mechanism of working. Mainly focused on the function of the heat source. Projects includes current information about heat pump market in Poland. Furthermore shows the development prospects. The whole concept design is confirmed by receiving energy from waste water flowing in the selected building.

W pracy została przeanalizowana możliwość wykorzystania kanału ściekowego jako ciepła odpadowego. Przedstawiono sposoby odbioru i ich miejsc. Ponadto została omówiona charakterystyka pompy ciepła z zasadą działania. Głównie skupiono się na funkcji dolnego źródła ciepła. Zawarto również aktualne dane odnośnie rynku pomp ciepła w Polsce oraz perspektyw jego rozwoju. Całość potwierdzona jest koncepcyjnym projektem odbioru niesionej energii ze ściekami w wybranym budynku.
Analysis of the possibility use sewer as a heat source for heat pumps power system hot water and central heating and selected conceptual design of the building
Keywords: pompa ciepła; dolne źródło ciepła; kanał ściekowy; ścieki; ciepło; heat pump; lower heat source; sewage system; sewage; heat